2016
DOI: 10.1080/21645515.2016.1245251
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications of nanoparticles in cancer immunotherapy

Abstract: In recent years considerable progress has been made in the field of cancer immunotherapy whereby treatments that modulate the body's own immune system are used to combat cancer. This has the potential to not only elicit strong anti-cancer immune responses which can break pre-existing tolerance and help promote tumor regression, but could also induce immunological memory which may help prevent tumor recurrence. In order to ensure effective delivery of immunotherapeutic agents, such as vaccines, checkpoint inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 125 publications
(128 reference statements)
0
28
0
Order By: Relevance
“…Some FDA-approved immune checkpoint agents are ipilimumab against CTLA-4, and pembrolizumab and nivolumab against PD-1. Lipid-based NPs are generally used to transport these materials to the target site [ 161 ]. A study showed that R848-loaded β —cyclodextrin NPs can efficiently be delivered to tumour-associated macrophages in vivo to macrophages to acquire an antitumourigenic M1-like phenotype.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Some FDA-approved immune checkpoint agents are ipilimumab against CTLA-4, and pembrolizumab and nivolumab against PD-1. Lipid-based NPs are generally used to transport these materials to the target site [ 161 ]. A study showed that R848-loaded β —cyclodextrin NPs can efficiently be delivered to tumour-associated macrophages in vivo to macrophages to acquire an antitumourigenic M1-like phenotype.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Consequently, immunoproteasome-deficient BMDCs showed impaired CP ability in vitro, as well as in vivo, in a mouse model [82]. The cytoplasmic delivery of exogenous proteins enhanced CP efficiency in a murine model [89]. Expression of PLC was higher in splenic cDC1s than in splenic cDC2s [44], and cDC1s were responsible for both cross-priming [44] and for cross-tolerance [90].…”
Section: Two Pathways For Cross-presentation (Cp)mentioning
confidence: 99%
“…The cytoplasmic delivery of exogenous proteins largely enhances CP efficiency [89], indicating that the retro-transport of internalized protein from endocytic compartments to the cytosol is one of the rate-limiting processes for an efficient CP. The intracellular transport pathways of extracellular proteins are different among DC subsets, such as cDC1s, moDCs, or BMDCs.…”
Section: The Non-classical Endosomementioning
confidence: 99%
See 1 more Smart Citation
“…These cationic lipid-assisted PEG-PLAbased NPs efficiently delivered siRNA into T cell in vitro and significantly increased the percentage of anti-tumour CD8 + T cells, while also decreasing the ratio of CD4 + FOXP3 + T reg among tumour infiltrating lymphocytes (TILs), resulting in the inhibition of tumour growth and prolonged survival time. 42,43 Finally, tumours can develop phenotypes that are less immunogenic.…”
Section: How Could Nps Be Used As a Booster For The Abscopal Effect?mentioning
confidence: 99%